1998
DOI: 10.1111/j.1574-695x.1998.tb01145.x
|View full text |Cite
|
Sign up to set email alerts
|

Protective efficacy of mycobacterial 71-kDa cell wall associated protein using poly (dl-lactide-co-glycolide) microparticles as carrier vehicles

Abstract: Microparticles composed of poly (DL-lactide-co-glycolide) (DL-PLG) were used as delivery vehicles for evaluating the immunoreactive and immunoprotective properties of 71-kDa cell wall associated protein of Mycobacterium tuberculosis H37Ra. Mice immunized with 71-kDa microparticles entrapped in DL-PLG (PLG-MPs) exhibited significantly higher T-cell stimulation and cytokine release in comparison to 71-kDa emulsified in Freund's incomplete adjuvant (FIA) as well as a BCG vaccinated group throughout the post-immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Controlled release devices have been used to encapsulate a large number of antigens against diseases as diverse as the plague [88,89], bacterial pneumonia [90], meningitis [91], tuberculosis [92], brucellosis [93], and anthrax [70]. On the whole, these studies demonstrate a similar adjuvant effect of controlled release devices that results in a stronger immune response, but with additional stability issues.…”
Section: Other Antigensmentioning
confidence: 97%
“…Controlled release devices have been used to encapsulate a large number of antigens against diseases as diverse as the plague [88,89], bacterial pneumonia [90], meningitis [91], tuberculosis [92], brucellosis [93], and anthrax [70]. On the whole, these studies demonstrate a similar adjuvant effect of controlled release devices that results in a stronger immune response, but with additional stability issues.…”
Section: Other Antigensmentioning
confidence: 97%
“…Another attempt at stabilising and protecting the Ag from damage during particle synthesis, by entrapping it in an oil‐based core of PLGA microparticles, resulted in a discrete in vitro release pattern with bursts after 3 or 7 weeks, depending on the L : G ratio in the PLGA particle composition [84]. A rare study investigating the protective efficacy of PLGA‐encapsulated mycobacterial protein (PLGA‐MP) against tuberculosis challenge in mice found significantly superior and longer lasting protection by PLGA‐MP when compared with the BCG vaccine and a small improvement over MP adjuvanted with incomplete Freund's adjuvant [85]…”
Section: Immunological Considerations Of Encapsulated Antigen Deliverymentioning
confidence: 99%
“…[84] A rare study investigating the protective efficacy of PLGA-encapsulated mycobacterial protein (PLGA-MP) against tuberculosis challenge in mice found significantly superior and longer lasting protection by PLGA-MP when compared with the BCG vaccine and a small improvement over MP adjuvanted with incomplete Freund's adjuvant. [85] Addition of adjuvants is another aspect of formulating encapsulated vaccines for delayed release and improving their immunogenicity. Using HBsAg as model antigen in mice, Singh et al demonstrated that encapsulated HBsAg results in immune responses comparable to three individual injections of HBsAg adsorbed to aluminium (Al)-based adjuvant, and these responses were maintained for over a year.…”
Section: Immunological Considerations Of Encapsulated Antigen Deliverymentioning
confidence: 99%
“…Antigens encapsulated within polymers can be released for a prolonged period at a controlled rate of polymer degradation (Vicent and Duncan, 2006). Polymers have been shown to be effective adjuvants for various antigenic proteins, including ovalbumin, cholera and tetanus toxoid, and malarial and pneumotrophic bacterial antigens (Dhiman and Khuller, 1998;Jaganathan et al, 2005). Poly(lactic acid-glycolic acid) (PLGA) is a polymer whose degradation rate and antigen release can be predicted (Jiang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%